DEFENDING ON ALL FRONTS: INTEGRATING THE THREAT RESPONSE MODEL INTO MULTI DOMAIN OPERATIONS - Alim, Hasmady (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The complexity of modern military operations necessitates innovative approaches to threat response models, particularly for nations like Malaysia facing diverse and evolving challenges. This article highlighted the integration of the Threat Response Model into Multi-Domain Operations (MDO) to enhance readiness, adaptability, and effectiveness. By aligning detection, assessment, and response capabilities across land, air, maritime, cyber, space, and information environments, the Malaysia Armed Forces (MAF) and other joint forces can achieve strategic and operational superiority in an increasingly complex battlespace. By addressing the unique requirements of the MAF, this model provides a foundation for future research and practical implementation. The article concludes, by adopting a threat response modal in multi-domain approach, aiming to support the modernization and adaptability of the MAF in response to contemporary modern warfare.